IR varieties and their impact (International rice research institute (IRRI), 2005)
Rice scientists, journalists, and historians often search for information on Green Revolution varieties of rice. In this sourcebook, World Food Prize Laureate, Dr. Gurdev S. Khush, and premier IRRI plant breeder, Dr. Parminder S. Virk, summarize the available information on 34 IR varieties. The book lists 328 IR breeding lines released as 643 varieties in 75 countries, irrespective of geographic location or ideology. It is estimated that 60 percent of the world rice area today is planted to IRRI-bred varieties or their progenies.